Reworking activity of the thalassinidean shrimp Trypaea australiensis Dana, 1852 (Decapoda: Pleocyemata: Callianassidae) in an Australian estuary: A pilot study. Issue 4 (16th November 2021) - Oncken, Nele Svenja; Croizeau, Tamara; Connolly, Rod M; Flindt, Mogens R; Kristensen, Erik
Abstract: Trypaea australiensis Dana, 1852 is the predominant bioturbating thalassinidean shrimp on the east coast of Australia. It is, like other large bioturbators, generally considered an important ecosystem engineer. The sediment particle reworking rate of thalassinideans, a key parameter in benthic biogeochemical modelling, nevertheless remains unknown. We have for the first time quantified particle reworking by a population of T. australiensis living in fine estuarine sand. The particle reworking rate was monitored for 18 days using coarse sand as a new tracer approach followed by analyses of grain-size distribution in the sediment to a depth of 24 cm. Burial depth (BD, cm) over time (t, days) followed the relationship BD = 0.3002 × t for an average population density of 96 individuals m –2, equivalent to a sediment displacement of 1.1 m 3 m –2 yr –1 (11.4 liters individual –1 yr –1 ). The individual-specific particle reworking by this thalassinidean is higher than that reported for most other key bioturbators, and its engineering impact on estuarine sediments therefore has potentially large consequences for biodiversity and ecosystem functioning.